1995
DOI: 10.1073/pnas.92.22.10197
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmas and oncogenesis: persistent infection and multistage malignant transformation.

Abstract: Oncogenic potential of human mycoplasmas was studied using cultured mouse embryo cells, C3H/10T1/2 (C3H). Mycoplasma fermentans and Mycoplasma penetrans, mycoplasmas found in unusually high frequencies among patients with AIDS, were examined. Instead of acute transformation, a multistage process in promotion and progression of malignant cell transformation with long latency was noted; after 6 passages (1 wk per passage) of persistent infection with M. fermentans, C3H cells exhibited phenotypic changes with mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
1
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 23 publications
6
171
1
3
Order By: Relevance
“…Another important point is that mycoplasmas have promitogenic activity 71,72 . On the other hand, a recent study 73 has shown that chlamydial infection inhibits apoptosis in the host cell.…”
Section: Discussionmentioning
confidence: 99%
“…Another important point is that mycoplasmas have promitogenic activity 71,72 . On the other hand, a recent study 73 has shown that chlamydial infection inhibits apoptosis in the host cell.…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma has been associated with many human diseases, such as pneumonitis and urinogenital infections [1][2][3]. Association between mycoplasma, carcinogenesis and metastasis has generally been supported although the underlying mechanism(s) remain an enigma [4][5][6][7][8]. Infectionrelated carcinogenesis, however, has been clearly documented with Helicobacter pylori, bacterium known to induce gastric cancer [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mycoplasmas are common contaminants of laboratory cell cultures that usually do not affect cell growth and therefore remain undetectable in the absence of molecular or immunological assays. However, long-term mycoplasma infections in cell cultures are associated with increased frequency of chromosomal instability and malignant transformation (Tsai et al, 1995;Feng et al, 1999;Cimolai, 2001). Thus, long-term infection with Mycoplasma fermentans or M. penetrans was reported to induce spontaneous transformation of mouse embryo fibroblasts in concert with overexpression of the H-ras and c-myc protooncogenes (Zhang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%